Analysis of renewable energy resources (RERs) under the China-Pakistan economic corridor (CPEC) initiative: A proposed solution for optimized and sustainable energy management - Rehman, Anis Ur; Alblushi, Ishaq G. Muhammad; Khalid, Haris M.; Said, Zafar; Ismail, Abdulla; Muyeen, S. M.; Abdelaziz, Almoataz Y. (Elsevier, 2025)
The western portion of Kashmir region faces challenges towards complete harness and integration of renewable energy resources (RERs) available in abundance. These challenges correlate effectively to the China-Pakistan Economic Corridor (CPEC) initiatives. To address these challenges, this article conducts a comprehensive analysis of smart grid technologies towards a possible energy solution for western Kashmir. The proposed research thoroughly examines: 1) energy generation, 2) energy consumption, and 3) energy market dynamics in the region. The findings emphasize the pivotal role of western Kashmir and highlight its substantial potential for RERs as a valuable contributor to CPEC energy initiatives. The dominance of hydroelectric power in the Alpha Case accounts for 97.6 % of total electric energy production and an impressive annual output of 100,372,080,000 kWh. This eventually demonstrates western Kashmir's capacity for generating substantial clean energy. The Beta Case portrays commendable self-sufficiency, eliminating the need for grid energy purchases and exemplifying sustainable practices. These findings offer invaluable insights to policymakers and stakeholders while providing a robust foundation for 1) effectively harnessing western Kashmir's RERs, 2) driving sustainable development, 3) fostering energy independence, and 4) positioning western Kashmir as a significant participant in the transition towards a low-carbon future and climate change. (c) 2017 ElsevierInc.Allrightsreserved.
Keywords: China-Pakistan economic corridor (CPEC); Economic growth; Energy management; Energy optimization; Renewable energy resources (RERs); Smart grid technologies; Sustainable development